1993
DOI: 10.3109/10715769309111600
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin Converting Enzyme Inhibitors as Oxygen Free Radical Scavengers

Abstract: The authors have compared the ability of two non-SH-containing angiotensin converting enzyme (ACE) inhibitors (enalaprilat and lisinopril) with an -SH containing ACE inhibitor (captopril) to scavenge the hydroxyl radical (.OH). All three compounds were able to scavenge .OH radicals generated in free solution at approximately diffusion-controlled rates (10(10) M-1 s-1) as established by the deoxyribose assay in the presence of EDTA. The compounds also inhibited deoxyribose degradation in reaction mixtures which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 20 publications
3
20
0
Order By: Relevance
“…For example, angiotensin II has been found to increase the activity of vascular NADH oxidase in the rat and, probably related to this, the vascular production of superoxide anions, while selective blockade of angiotensin type I receptors reduced superoxide production (39). These studies extend previous observations of antioxidant effects of ACE inhibitor drugs (40)(41)(42)(43) and suggest that suppression of superoxide production is likely to be particularly relevant in the diabetic state (31)(32)(33). Additionally, decreased production of angiotensin II could act through protein kinase C and consequent increase in NO synthase activity, leading to increased NO synthesis (34).…”
Section: Discussionsupporting
confidence: 78%
“…For example, angiotensin II has been found to increase the activity of vascular NADH oxidase in the rat and, probably related to this, the vascular production of superoxide anions, while selective blockade of angiotensin type I receptors reduced superoxide production (39). These studies extend previous observations of antioxidant effects of ACE inhibitor drugs (40)(41)(42)(43) and suggest that suppression of superoxide production is likely to be particularly relevant in the diabetic state (31)(32)(33). Additionally, decreased production of angiotensin II could act through protein kinase C and consequent increase in NO synthase activity, leading to increased NO synthesis (34).…”
Section: Discussionsupporting
confidence: 78%
“…ACE inhibitors including captopril have proven to be beneficial in experimental autoimmune encephalomyelitis (Constantinescu et al, 1995), myocarditis (Godsel et al, 2003), adriamycin-induced myocardial and hematological toxicities (O. Al-Shabanah et al, 1998), Freund`s adjuvant arthritis (Agha and Mansour, 2000) and experimental rats` colitis (Jahovic et al, 2005). The ability of captopril to act as a reactive oxygene species (ROS) scavenger (Mira et al, 1993) was found to be of major importance in its protection against ischemia-reperfusion-induced arrhythmias (Birincioglu et al, 1997) and liver injury in rats (Gulluoglu et al, 1996). An anti-tumor, antifibrotic and cytoprotective effects of captopril have also been demonstrated (Williams et al, 2005;Regan et al, 1996;Murley et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…According to some authors, only ACE inhibitors with a sulphhydryl group are capable of scavenging ROS, 52,53 whereas others suggest that the free radical scavenging properties are independent of the sulphhydryl group. [54][55][56][57] Although ACE inhibitors such as captopril are potent free radical scavengers in vitro, a scavenger action in vivo is unlikely. In the DATATOP (Deprenyl and Tocopherol Antioxidant Therapy of Parkinson's disease) study, two antioxidants, i.e.…”
Section: Introductionmentioning
confidence: 99%